2021
DOI: 10.1038/s41598-021-89758-4
|View full text |Cite|
|
Sign up to set email alerts
|

Non-invasive assessment of exfoliated kidney cells extracted from urine using multispectral autofluorescence features

Abstract: Optimally preserved urinary exfoliated renal proximal tubule cells were assessed by multispectral imaging of cell autofluorescence. We demonstrated different multispectral autofluorescence signals in such cells extracted from the urine of patients with healthy or diseased kidneys. Using up to 10 features, we were able to differentiate cells from individuals with heathy kidneys and impaired renal function (indicated by estimated glomerular filtration rate (eGFR) values) with the receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The utility of exfoliated PTCs from urine has proven to be clinically valuable in prognosticating the degree of disease for various tubular diseases that are associated with CKD, including conditions with a genetic predisposition [ 22 , 50 , 51 ]. It is suggested that exfoliated PTCs from urine may represent the degree of pathology in the kidneys [ 22 , 52 ]. Previous studies noted the number of exfoliated PTCs correlating with kidney function decline in DKD, though this may not correspond to the degree of kidney injury in all cases [ 52 , 53 ].…”
Section: Exfoliated Proximal Tubule Cellsmentioning
confidence: 99%
“…The utility of exfoliated PTCs from urine has proven to be clinically valuable in prognosticating the degree of disease for various tubular diseases that are associated with CKD, including conditions with a genetic predisposition [ 22 , 50 , 51 ]. It is suggested that exfoliated PTCs from urine may represent the degree of pathology in the kidneys [ 22 , 52 ]. Previous studies noted the number of exfoliated PTCs correlating with kidney function decline in DKD, though this may not correspond to the degree of kidney injury in all cases [ 52 , 53 ].…”
Section: Exfoliated Proximal Tubule Cellsmentioning
confidence: 99%
“…Proximal tubule cells (PTCs) were extracted from the urine (100ml) of the above 2 groups using immunomagnetic separation with antibodies against aminopeptidase N (CD13) and sodium/glucose co-transporter 2 (SGLT2) as we have previously described (8). Briefly, urine was spun at 3000/4000 rpm for 20 min (at 4 o C) to pellet the urinary exfoliated cells, which were then washed twice with phosphate buffered saline (PBS).…”
Section: Renal Proximal Tubule Cell Isolation From Urinementioning
confidence: 99%
“…To confirm specific isolation of PTCs, an aliquot of isolated cells was incubated with antibodies against CD13, SGLT2 and angiotensinogen (AGT) at 4°C overnight as we have previously described (8). They were then washed with PBS and stained with the relevant secondary antibodies.…”
Section: Confocal Microscopymentioning
confidence: 99%
See 2 more Smart Citations